Liver transplantation vs liver resection in HCC: promoting extensive collaborative research through a survival meta-analysis of meta-analyses - Martinino, Alessandro; Bucaro, Angela; Cardella, Francesca; Wazir, Ishaan; Frongillo, Francesco; Ardito, Francesco; Giovinazzo, Francesco (Frontiers in Oncology, 2024)
Background: HCC is a major global health concern, necessitating effective treatment strategies. This study conducts a meta-analysis of meta-analyses comparing liver resection (LR) and liver transplantation (LT) for HCC. Methods: The systematic review included meta-analyses comparing liver resection vs. liver transplantation in HCC, following PRISMA guidelines. Primary outcomes included 5-year overall survival (OS) and disease-free survival (DFS). AMSTAR-2 assessed study quality. Citation matrix and hierarchical clustering validated the consistency of the included studies. Results: A search identified 10 meta-analyses for inclusion. The median Pearson correlation coefficient for citations was 0.59 (IQR 0.41-0.65). LT showed better 5-year survival and disease-free survival in all HCC (OR): 0.79; 95% CI: 0.67-0.93, I^2:57% and OR: 0.44; 95% CI: 0.25-0.75, I^2:96%). Five-year survival in early HCC and ITT was 0.63 (95% CI: 0.50-0.78, I^2:0%) and 0.60 (95% CI: 0.39-0.92, I^2:0%). Salvage LT vs. Primary LT did not differ between 5-year survival and disease-free survival (OR: 0.62; 95% CI: 0.33-1.15, I^2:0% and 0.93; 95% CI: 0.82-1.04, I^2:0%). Conclusion: Overall, the study underscores the superior survival outcomes associated with LT over LR in HCC treatment, supported by comprehensive meta-analysis and clustering analysis. There was no difference in survival or recurrence rate between salvage LT and primary LT. Therefore, considering the organ shortage, HCC can be resected and transplanted in case of recurrence.